Biliary Interventions: Tools and Techniques of the Trade, Access, Cholangiography, Biopsy, Cholangioscopy, Cholangioplasty, Stenting, Stone Extraction, and Brachytherapy - Ahmed, Osman; Mathevosian, Sipan; Arslan, Bulent (Seminars in Interventional Radiology, 2016)
Therapeutic access to the biliary system is generally limited to endoscopic or percutaneous approaches. A variety of percutaneous transhepatic biliary interventions are applicable for the diagnosis and treatment of biliary system pathologies, the majority of which may be performed in conjunction with one another. The backbone of nearly all of these interventions is percutaneous transhepatic cholangiography for opacification of the biliary tree, after which any number of therapeutic or diagnostic modalities may be pursued. We describe an overview of the instrumentation and technical approaches for several fundamental interventional procedures, including percutaneous transhepatic cholangiography and internal/external biliary drainage, endobiliary biopsy techniques, cholangioscopy, cholangioplasty and biliary stenting, biliary stone extraction, and intraluminal brachytherapy.
Keywords: biliary interventions; cholangiography; cholangioplasty; biliary stenting; interventional radiology